The effect of financial leverage on firm profitability and working capital management in the Asia- Pacific Region - Anya Deshpande (The Central European Review of Economics and Management (CEREM), 2023)
Aim: The main aim of this article is to examine the impact of financial leverage on firm profitability and working capital management of Asia-Pacific (APAC) firms listed in the United States and the United Kingdom. Design / Research methods: The regression analyses are conducted with panel data over the period of 2013-2022 using the Ordinary Least Squares method. Historical financial data has been obtained by using Refinitiv Eikon. In addition to quantitative research, this study also provides case examples. Conclusions / findings: The findings reveal that for APAC firms listed internationally, financial leverage has a negative relationship with firm profitability and a positive relationship with working capital levels. The study emphasizes the complex nature of financial leverage as a double-edged sword, capable of shaping the trajectories of APAC firms navigating the international business arena. Originality / value of the article: Although the effect of financial leverage on firm profitability has been researched before, it has not been researched on the Asia-Pacific region as a whole, specifically for the companies that are listed internationally. Furthermore, the effect of financial leverage on working capital management is scant overall and has rarely been examined distinctively, especially in this particular geographical region.
Keywords: G32; 330; Leverage; Working Capital Management; Cash Conversion Cycle; Firm Profitability; Asia-Pacific; International Listings